The Bangladesh garment industry and the global supply chain choices and constraints of management - Rahman, Shahidur (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book analyses the choices and constraints of management within the Bangladesh garment industry and how management negotiates these challenges to ensure the global garment supply chain is sustainable. Exploring the international South Asian garment industry and using middle management and the owners of Bangladeshi factories as a case study, the book assesses the limits and costs of globalization for Bangladesh and outlines the challenges of the fast fashion business model for the global market. The book focuses on the changing dynamics of the entrepreneur class, how they manage factories and their experiences with Accord-Alliance and the challenges of sustainability. Within these four broader themes, the author critically examines management strategies towards compliance and labour productivity, transnational governance, buyer-supplier relationships and power dynamics. This book is the first to explore management's perceptions of workers, buyers and government through an analysis of four factories which demonstrate the role of mid-level management, how supervisors treat production workers, workers' impact on innovation, welfare programmes as well as CSR policies and the impact of COVID-19. Offering new perspectives on Bangladesh's garment export industry, this book will be of interest to researchers in the field of policy studies, labour studies, South and Southeast Asian studies, development studies, international trade, and political science"--
From LDC to Lower Middle Income Country -- From Million to Billion dollar industry -- From First generation to Second generation Entrepreneurs -- Case study: Small garment factory -- Case study: Medium and Large Factory -- Transnational Governance: Accord and Alliance -- Challenges of Sustainability -- Road Ahead.
Off-Campus Access: Athens ID and Password Required
On-Campus Access: No User ID or Password Required
Includes bibliographical references and index.
ESS
Mode of access: Internet
Keywords: Clothing trade -- Bangladesh; Clothing workers -- Bangladesh; Economic development -- Bangladesh; Bangladesh -- Commerce; Electronics book